2014
DOI: 10.1007/978-3-319-08105-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Local Fractal Functions and Function Spaces

Abstract: Abstract. We introduce local iterated function systems and present some of their basic properties. A new class of local attractors of local iterated function systems, namely local fractal functions, is constructed. We derive formulas so that these local fractal functions become elements of various function spaces, such as the Lebesgue spaces L p , the smoothness spaces C n , the homogeneous Hölder spacesĊ s , and the Sobolev spaces W m,p .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…The next result is a special case of Theorem 1 in [16] and its validity follows directly from the above considerations.…”
Section: A Fractal-type Operation Of Fractal Functionsmentioning
confidence: 73%
“…The next result is a special case of Theorem 1 in [16] and its validity follows directly from the above considerations.…”
Section: A Fractal-type Operation Of Fractal Functionsmentioning
confidence: 73%
“…The research reported here is admittedly influenced to an extent by works on fractal functions and local fractal functions by Massopust; see [6,7]. However, it should be noted that our exposition aims at a different goal.…”
Section: Introductionmentioning
confidence: 93%
“…For 0 < p < 1, f p defines only a quasi-norm on L p (I) and L p (I) is complete with respect to the metric d p (f, g) := f − g p p . References [10,11] provided us with basic tools which we have modified and adapted to prove:…”
Section: Fractal Functions In L P -Spaces Revisitedmentioning
confidence: 99%